SAMHD1 is recurrently mutated in T-cell prolymphocytic leukemia - Johansson, Patricia; Klein-Hitpass, Ludger; Choidas, Axel; Habenberger, Peter; Mahboubi, Bijan; Kim, Baek; Bergmann, Anke; Scholtysik, René; Brauser, Martina; Lollies, Anna; Siebert, Reiner; Zenz, Thorsten; et al. (Blood cancer journal, 2018)
T-cell prolymphocytic leukemia (T-PLL) is an aggressive malignancy with a median survival of the patients of less than two years. Besides characteristic chromosomal translocations, frequent mutations affect the ATM gene, JAK/STAT pathway members, and epigenetic regulators. We here performed a targeted mutation analysis for 40 genes selected from a RNA sequencing of 10 T-PLL in a collection of 28 T-PLL, and an exome analysis of five further cases. Nonsynonymous mutations were identified in 30 of the 40 genes, 18 being recurrently mutated. We identified recurrently mutated genes previously unknown to be mutated in T-PLL, which are SAMHD1, HERC1, HERC2, PRDM2, PARP10, PTPRC, and FOXP1. SAMHD1 regulates cellular deoxynucleotide levels and acts as a potential tumor suppressor in other leukemias. We observed destructive mutations in 18% of cases as well as deletions in two further cases. Taken together, we identified additional genes involved in JAK/STAT signaling (PTPRC), epigenetic regulation (PRDM2), or DNA damage repair (SAMHD1, PARP10, HERC1, and HERC2) as being recurrently mutated in T-PLL. Thus, our study considerably extends the picture of pathways involved in molecular pathogenesis of T-PLL and identifies the tumor suppressor gene SAMHD1 with ~20% of T-PLL affected by destructive lesions likely as major player in T-PLL pathogenesis.